A casual Model of promoting resilience in long-term recovery phase among Nepalese elderly citizens experiencing Disaster. - Timalsina, Rekha (2021)
ABSTRACT: Considering the high risk of natural disasters in Nepal and the psychological vulnerability of elderly citizens in disasters, a cross-sectional path analytical study design was adopted to develop and test the hypothesized causal model of promoting resilience in the long-term recovery phase among 324 randomly selected Nepalese elderly citizens aged>- 65 years old experiencing a disaster. Two endogenous variables (self-efficacy and resilience) and eight exogenous variables (self-esteem, optimism, mental health, life satisfaction, perceived stress, loneliness, spiritually, and social support) were included in the hypothesized causal model. After receiving ethical approval from Thailand and Nepal, data were collected by sing ten sets of valid and reliable standard instruments for measuring exogenous and endogenous variable. After testing assumptions for multiple regression analysis and path analysis, the mental health variable was omitted from the hypothesized causal model to deal with the multicollinearity effect. Finally, the assessment of the model fit and illustration of the relationship by path diagram was done among 303 cases after deleting 21 cases of multivariate influential outlets. The findings revealed that the hypothesized causal model did not fit with the data of the current study. However, the final model was modified by adding one path from perceived stress to self-efficacy to show a better-fit of the model with the empirical data. The modified model explained 74.7% of variance by(1) self-efficacy, (2) perceived stress (3) spiritually, (4) self-esteem, and (5) social support on resilience (R2= .747). Further, the findings showed the significant direct and positive effect of spirituality (β= .08,p=013), and self-efficacy (β= .62, p=.000) on resilience, and the significant direct and negative effect of perceived stress (β= -.23, p=000) on resilience. Additional, the significant indirect and positive effect of self-esteem (β = .22,p =.002), and social support (β= .09, p=.005) on resilience, were proved via self-efficacy. The significant and positive total effects of the path from self-esteem to resilience through self-efficacy were evident (β= .29, p=.002) except for social support. Further, the indirect and negative effect of perceived stress (β= -.19, p=.002) on resilience was proved via self-efficacy. In additional, the significant and negative total effects of the paths from perceived stress to resilience were evident via self-efficacy (β= -.42, p=.002). According to these findings, resilience-focused nurse-led interventions or services should be premeditated to enhance self-efficacy, self-esteem, and spiritually; lower the perceived stress, and promote social support for fostering the resilience of Nepalese elders. In addition, the utilization of these findings will guide to provide need-based care and foster positive and successful psychosocial and spiritual adaptation in the face of adversities in a long-term post-disaster phase. Keywords: Disaster, Elderly citizens, Long-term, Recovery phase, Resilience